COVID-19 Impact on French Labor Market : Regional and Sectoral Shifts in Employment - Chavet, Noémie; Zeynalov, Ayaz; Pantea, Smaranda; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis investigates the complex effects of the COVID-19 pandemic on the French labor market, focusing on regional and sectoral disparities. It fills a gap in existing literature by using a mixed-method approach that combines theoretical and empirical data to explore how the pandemic altered employment patterns and economic resilience across various French regions and sectors. The study identifies significant shifts in employment dynamics, including a greater reliance on remote work and changes to employment contract structures. It highlights that the pandemic has deepened existing inequalities, affecting low-wage, temporary, and young workers most severely. Regionally, the most substantial economic downturns occurred in areas reliant on tourism, hospitality, and entertainment. These regional impacts were influenced by factors such as economic orientation, industrial composition, urban-rural dynamics, pre-pandemic economic health, workforce skills, innovation capabilities, and entrepreneurial activity. Sectorally, while public administration, agriculture, and construction showed employment stability, tourism and entertainment experienced dramatic reductions in paid hours and employment levels. The study shows that those sector-specific effects were driven by operational needs, adaptability to remote work, dependence on global supply chains, the essential nature of services, and company size. Additionally, the thesis assesses the effectiveness of government interventions in mitigating economic damage, suggesting a need for more targeted and robust policies to address vulnerabilities revealed by the pandemic. This aspect of the research contributes to a deeper understanding of the interplay between government action and economic outcomes during health crises.
Overall, the research offers insights into the pandemic's economic impacts and provides recommendations for policymakers to strengthen labor market resilience and equity, preparing for future crises.
Vedoucí práce: Ayaz Zeynalov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses